2021
DOI: 10.3389/fpsyg.2021.648478
|View full text |Cite
|
Sign up to set email alerts
|

Correction by Focus: Cleft Constructions and the Cross-Linguistic Variation in Phonological Form

Abstract: A challenging issue of cross-linguistic variation is that the same syntactic construction may appear in different arrays of contexts depending on language. For instance, cleft constructions appear with contrastive focus in English, but in a larger array of contexts in French. A part of the cross-linguistic variation may be due to prosodic differences, since prosodic possibilities determine the array of focus structures that can be mapped onto one and the same syntactic configuration. In the present study, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Previous studies have found that L1 Mandarin and English listeners weight cues to focus differently, with prosodic cues being stronger than clefting in L1 Mandarin and the reverse in English (Calhoun et al, 2021;Chen et al, 2012;Greif & Skopeteas, 2021;Yan & Calhoun, 2020). To the best of our knowledge, however, no research has investigated how these interact in L2 processing.…”
mentioning
confidence: 92%
“…Previous studies have found that L1 Mandarin and English listeners weight cues to focus differently, with prosodic cues being stronger than clefting in L1 Mandarin and the reverse in English (Calhoun et al, 2021;Chen et al, 2012;Greif & Skopeteas, 2021;Yan & Calhoun, 2020). To the best of our knowledge, however, no research has investigated how these interact in L2 processing.…”
mentioning
confidence: 92%